Unveiling the Necrocapitalist Dimensions of the Shadow Carceral State: On Pay-to-Stay to Recoup the Cost of Incarceration. (February 2021) - Friedman, Brittany
The expansion of monetary sanctions constitutes what Beckett and Murakawa describe as the "shadow carceral state, " where covert penal power is expanded through institutional annexation by blending civil, administrative, and criminal legal authority. A growing body of work on monetary sanctions has begun to dissect covert penal power by tracing increased civil and administrative pipelines to incarceration, civil financial alternatives to criminal sanctions, and innovations to generate criminal justice revenue. However, institutional annexation and innovation in the form of contemporary pay-to-stay practices remain understudied and undertheorized. In this article, I first examine statutes and practices to theorize pay-to-stay as exemplary of the shadow carceral state—an outcome of legal hybridity and institutional annexation legitimated using the legal construction of "not punishment, " which frames monetary sanctions as non-punitive. Second, I expand Beckett and Murakawa's framework to argue pay-to-stay practices reveal how the shadow carceral state compounds or initiates the civil death of those charged. I broaden our notion of civil death to include financial indebtedness to the shadow carceral state. I suggest covert penal power expands through the accumulation of resources extracted from people marked for civil death through criminal justice contact. Finally, I conclude that monetary sanctions such as pay-to-stay reveal how the shadow carceral state expands covert penal power through necrocapitalism, meaning institutional accumulation occurs through dispossession and the subjugation of life to the power of death.